Pengaruh Model Pembelajaran Survey Qustion Read Recite Review (SQ3R) Terhadap Kemampuan Representasi Matematis Peserta Didik SMA Ditinjau Dari Kemampuan Awal Matematika - Sofwan Munawar; Yuyu Yuhana; Cecep Anwar Hadi Firdos Santosa (Universitas Sultan Ageng Tirtayasa, 2020)
This research is motivated by the importance of mathematical representation ability as one of five abilities that must be possessed by students in learning mathematics. The purpose of this study is to determine the effect of Survey, Questions, Read, Recite, Review (SQ3R) learning models on the mathematical representation ability of high school students. This research is a quantitative research with quasi-experimental method and pretest posttest control group design. The instrument used was a test of mathematical representation ability. The results of this study are differences in mathematical representation ability of students who get the SQ3R learning model is higher than students who get a direct learning model. Keywords: Mathematical Representations Ability, SQ3R Learning, Direct Learning